"Frank" presentations as a novel research construct and element of diagnostic decision‐making in autism spectrum disorder. Issue 4 (21st October 2016) - de Marchena, Ashley; Miller, Judith
Abstract : Many individuals with ASD have a distinctive behavioral presentation that is recognizable within moments, a phenomenon we call "frank" ASD. This phenomenon has been discussed informally for decades, perhaps as "classic" ASD; however, there is no unitary "classic" presentation, and classic autism does not seem to correspond to level of functioning. Thus, neither "frank" nor "classic" autism has been delineated or studied as a research construct. To initiate the empirical study of frank ASD, we surveyed 151 clinicians, from a range of disciplines that diagnose ASD, about this phenomenon. Respondents completed a 13‐item questionnaire about frank ASD, which was analyzed using a mixed‐methods approach. Ninety‐seven percentage of respondents were familiar with the phenomenon. Respondents estimated that 40% of the ASD population has a frank presentation. Respondents reported the most highly specific behaviors associated with frank presentations were a general sense of impaired reciprocity, quality of eye contact, atypical vocal prosody, presence of motor mannerisms, and atypical gait or posture. In general, respondents reported detecting frank features rapidly, with the majority forming their impressions within the first ten minutes of interaction or observation. Although unstudied empirically, "frank" presentations of ASD are familiar to diagnosing clinicians, and appear to be based on behaviors both central to ASD diagnostic criteria (e.g., impaired reciprocity), and absent from diagnostic criteria (e.g., atypical gait or posture). We discuss these findings within the context of diagnostic decision‐making and behavioral phenotyping of ASD. Autism Res 2016, . © 2016 International Society for Autism Research, Wiley Periodicals, Inc. Autism Res 2017, 10: 653–662 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.